Baksos Donor Darah dan Charity Pasar Murah Sembako: Wujud Kepedulian Lions Club Medan Angkasa dalam Mendukung Ketahanan Pangan dan Kesehatan Masyarakat di Kota Medan - Endy Juli Anto; Tim Lions Club Medan Angkasa; Steven Tjendra; Enney; Ronald T. H. Tambunan,; Frengky S. Manullang; Widjaya Taufik Tiji; Tengku M. Fauzi; Jadeny Sinatra; Juli Jamnasi; Jekson Martiar Siahaan (Universitas Methodist Indonesia, 2026)
Voluntary blood donation and food assistance programs are two critical pillars of community service that address healthcare and socioeconomic disparities simultaneously. This community service activity, conducted by Lions Club Medan Angkasa (District 307 A2) in collaboration with PMI Kota Medan, aimed to increase blood stock availability while alleviating food insecurity among underprivileged communities in Medan. The combined event —